Kepastian Hukum Kedudukan Akta Jual Beli (AJB) Sebagai Dasar Gugatan - Friko Rumadanu; Gunawan Djajaputra (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
The Sale and Purchase Deed (AJB) is an important document in property sale and purchase transactions, especially land and buildings, which serves as legal evidence of the transfer of ownership rights from the seller to the buyer. As an authentic deed made by a Land Deed Official (PPAT), AJB has higher legal force compared to private deeds, thus providing stronger legal protection for both parties. The AJB creation process involves thorough verification of various required documents, such as land certificates, proof of tax payment, and identity documents, to ensure that the transactions carried out are legally valid. PPAT plays an important role in checking the validity of land, both in terms of legality and legal status, in order to avoid potential disputes in the future. After the AJB is ratified, this document becomes the basis for submitting an application to change the name of the owner on the land certificate at the National Land Agency (BPN). This process ensures that the data recorded on the certificate corresponds to legal reality, recognizing the buyer as the legal owner of the property. AJB also functions as legal evidence if there is a dispute regarding ownership, for example, a claim by a third party claiming to be the owner or if there is an error in the transaction process. In this case, AJB can be used to prove that the transfer of ownership rights has been carried out in accordance with applicable regulations. As an authentic document, the AJB is an important first step in ensuring the legality of property ownership and protecting the buyer's rights from potential legal problems in the future. Verification carried out by PPAT and the use of AJB in the land certificate transfer process provide legal certainty and reduce the risk of disputes related to the property purchased.